A review of the leafhopper genus Subulatus Yang & Zhang (Hemiptera: Cicadellidae: Evacanthinae) , with description of a new species from China - Li, Yu-Jian; Li, Zi-Zhong; Yang, Mao-Fa (Zootaxa, 2015)
The species of the Oriental leafhopper genus Subulatus Yang & Zhang are reviewed. A new species, Subulatus flavidus sp. nov., from Yunnan Province, China is described and a key to all known species of Subulatus is provided.